Relación entre el nivel de conocimiento en soporte vital básico y el tiempo de experiencia profesional de los enfermeros de la segunda especialidad de emergencias y desastres de la UNT - López Quezada, Lander Antonio (2015)
The present investigation descriptive, correlational and crosssectional, was performed in order to establish the relationship of level of knowledge of Basic Life Support and Time Professional Experience Nurses, students of the specialty of Emergency and Disaster UNT. The sample universe consisted of 34 nurses who met the inclusion criteria for data collection questionnaire "Level of Knowledge on Basic Life Support and Time Professional Experience" is used The information obtained was processed in tables of single and double entrance; for statistical analysis of the Test of Independence Criteria (X2) was used, Results show that 88% have a regular level of knowledge of Basic Life Support Life and 12% a low level of knowledge Regarding time professional experience 76% are between 1- 2 years, 21% over 3 years and 3% less than 1 year. Concluding that the level of knowledge in basic life support no significant relationship with time professional experience